Characteristics of Pore-Water Pressure Response in Slopes During Rainfall - Alfrendo Satyanaga Nio (Jurnal Teknik Sipil, 2007)
Field measurements of residual soil slopes are valuable for the assessment of slope stability during rainfall. Several residual soil slopes, which are predominantly unsaturated due to their deep groundwater table, were instrumented with tensiometer and rainfall gauge in order to study the response characteristics of the slopes during rainfall. Comprehensive field measurement results involving a large number of rainfall events are presented in the paper. The results show that the pore-water pressures in all instrumented slopes increased in a similar fashion during rainfall, but at different magnitudes depending on soil type. The pore-water pressure response characteristics can then be used to estimate the variation in factor of safety of the slope during rainfall.